2020
DOI: 10.1016/j.tine.2019.100124
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of neurobehavioral traits and cognitive ability to academic achievement in higher education

Abstract: Background: People vary between each other on several neurobehavioral traits, which may have implications for understanding academic achievement. Methods: University-level Psychology or Engineering students were assessed for neurobehavioral traits, intelligence, and current psychological distress. Scores were compared with their grade point average (GPA) data. Results: Factors associated with higher GPA differed markedly between groups. For Engineers, intelligence, but not neurobehavioral traits or psychologic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 105 publications
(138 reference statements)
2
8
0
Order By: Relevance
“…This may be one way in which mixed-handedness could convey a small advantage in higher education. We have previously shown in the same sample as reported here, that the modulation of memory processes is a significant predictor of academic grades [18]. In addition, a study of foreign language acquisition, that mimicked natural language learning, found that the amount of learning was proportional to degree of mixed-handedness of the participants [99].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This may be one way in which mixed-handedness could convey a small advantage in higher education. We have previously shown in the same sample as reported here, that the modulation of memory processes is a significant predictor of academic grades [18]. In addition, a study of foreign language acquisition, that mimicked natural language learning, found that the amount of learning was proportional to degree of mixed-handedness of the participants [99].…”
Section: Discussionsupporting
confidence: 79%
“…Written informed consent was provided by all participants, in line with the local ethics committee approved protocol. First basic demographic information was recorded and then all participants completed several cognitive tests (reported previously) [18], and also the MMT as a measure of intelligence. The questionnaires were supplied as a booklet and completed by hand during the test session.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second meta-analysis, we compared non-right-handedness rates (i.e., lefthandedness and mixed-handedness combined) between individuals with ADHD and controls. Overall, k = 16 studies were included (Dramsdahl et al 2012;Groen et al 2009;Hotham et al 2018;Neely et al 2016;Neely et al 2017;Martel et al 2008;Pluck et al, 2020;Robaey et al 1992;Rolfe et al 2006;Shaw and Brown 1990;Scharoun et al 2013;Soliva et al 2010;ter Huurne et al 2013;Tucha et al 2008;Tucha et al 2006;Xia et al 2012) and d = 6 databases (ADHD-200, Würzburg, Niche, ACPU, NICAP, IMpACT2).…”
Section: Discussionmentioning
confidence: 99%